A Metafunction Analysis of Conjunction System in the Opinion Forum of the Jakarta Post Daily Newspaper - Pikir Wisnu Wijayanto (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
The study aims at finding the meaning of the texts or sentences in detail from the discourse semantics’ perspectives through metafunctions analysis of conjunction systems introduced by Martin and Rose (2003: 110). This study used qualitative and descriptive methods. The data used in this study is taken from the top three most shared articles by the readers in the